2017
DOI: 10.1111/hdi.12620
|View full text |Cite
|
Sign up to set email alerts
|

The effect of small dose of topiroxostat on serum uric acid in patients receiving hemodialysis

Abstract: It is suggested that a low dose of topiroxostat decreased serum uric acid sufficiently to maintain it below 7.0 mg/dL in patients receiving hemodialysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 24 publications
0
2
0
2
Order By: Relevance
“…The results of a new trial (Effect of Xanthine Oxidase Inhibitor in Chronic Heart Failure Patients Complicated with Hyperuricemia study – Excited-UA) study carried out on heart failure patients are soon expected [68]. Topiroxostat has also been demonstrated to significantly and safely decrease SUA levels in hyperuricemic patients receiving hemodialysis at the minimum dose compared to allopurinol ones [69]. Moreover, since topiroxostat is not dialyzable, unlike the other XOIs, the dose reduction is not required even in patients with lowered renal function [70].…”
Section: Xo Inhibitorsmentioning
confidence: 99%
“…The results of a new trial (Effect of Xanthine Oxidase Inhibitor in Chronic Heart Failure Patients Complicated with Hyperuricemia study – Excited-UA) study carried out on heart failure patients are soon expected [68]. Topiroxostat has also been demonstrated to significantly and safely decrease SUA levels in hyperuricemic patients receiving hemodialysis at the minimum dose compared to allopurinol ones [69]. Moreover, since topiroxostat is not dialyzable, unlike the other XOIs, the dose reduction is not required even in patients with lowered renal function [70].…”
Section: Xo Inhibitorsmentioning
confidence: 99%
“…Febuxostat is also presumed to inhibit the same enzymatic center [6]. It was reported that topiroxostat 60 mg/day provided sUA-lowering e cacy as well as febuxostat 40 mg/day in CKD patients [7]. It was also reported that topiroxostat 20 mg/day lowered sUA in most of the patients even with advanced CKD [8].…”
Section: Discussionmentioning
confidence: 99%
“…Дослідження FOCUS продемонструвало послідовне стабільне зниження концентрації СК під впливом фебуксостату: у перший рік лікування цільового рівня досягли 78% пацієнтів, на другий рік -76%, на третій та четвертий роки -84 та 90% відповідно; протягом перших 2 років знизилися потреба у протизапальній терапії та частота загострень. У 76,9% хворих, які мали на момент включення в дослідження тофуси, через 4 роки констатовано їхнє повне розсмоктування [27]. У 2019р.…”
Section: вступunclassified